2019
DOI: 10.1530/eje-18-0844
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal venous sampling: cosyntropin stimulation or not?

Abstract: Notwithstanding the high prevalence of primary aldosteronism (PA), probably the most common form of secondary hypertension, the diagnosis of PA is often neglected or delayed, thus precluding target treatment, which is curative in many cases. For selection of the most appropriate treatment, a fundamental step is the distinction between a lateralized form, mainly aldosterone-producing adenoma (APA), and bilateral adrenocortical hyperplasia (BAH), also known as idiopathic hyperaldosteronism (IHA). To this aim all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 45 publications
5
39
2
1
Order By: Relevance
“…The use of ACTH in AVS remains controversial and has recently been reviewed by Deinum et al 20 An earlier review by Rossi et al 21 demonstrated increased cannulation success at the expense of reduced lateralization. In agreement with Rossi's review and a meta‐analysis, 11 our study also showed a decrease in lateralization indices between baseline and post‐ACTH at both centres (13% at Austin Health and 17% at Monash Health).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ACTH in AVS remains controversial and has recently been reviewed by Deinum et al 20 An earlier review by Rossi et al 21 demonstrated increased cannulation success at the expense of reduced lateralization. In agreement with Rossi's review and a meta‐analysis, 11 our study also showed a decrease in lateralization indices between baseline and post‐ACTH at both centres (13% at Austin Health and 17% at Monash Health).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that AVS with ACTH stimulation did not significantly reduce the number of incorrect lateralization but significantly reduced the number of unsuccessful cannulations compared with AVS without ACTH stimulation ( 57 ). However, the evidence is still limited and under debate which is beyond the scope of this review and can be found in prior review literature ( 58 ).…”
Section: Acth Stimulation Test For the Diagnosis Of Primary Aldosteromentioning
confidence: 99%
“…Although AVS is accepted as the gold standard test for subtyping PA, the procedure is underused especially in underdeveloped areas partially because the AVS procedure is technically challenging and relatively expensive [9]. Due to the anatomical complexity and variations, AVS fails frequently even in experienced hands [10].…”
Section: Introductionmentioning
confidence: 99%